2008
DOI: 10.3349/ymj.2008.49.3.486
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ultra Low Molecular Weight Heparin on Glutamate-Induced Apoptosis in Cortical Cells

Abstract: PurposeTo investigate the effect of ultra low molecular weight heparin (ULMWH) on glutamate induced apoptosis in rat cortical cells and to explore the possible mechanisms.Materials and MethodsCell viability was measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Apoptosis was first analyzed with Hoechst 33258 and then confirmed by DNA fragmentation. The concentration of free intracellular calcium ([Ca2+]i) was determined with fura-2/AM fluorometry. The expression of Bcl-2 family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Explant-induced apoptosis of glomerular cells was similarly protected by acute treatment with heparin in vitro (42), and we speculate that this early damage may also be attributable to matrix detachment. Furthermore, ultra-low-molecular weight heparin has been reported to prevent glutamate-induced apoptosis in brain cortical cells in vitro and to prevent free radical-induced damage after ischemia/reperfusion injury in rat brain in vivo (43,44). Our demonstration that HS replacement by heparin rescued β cells from free radical damage and apoptosis in vitro is consistent with these prior reports and with the notion that islets/β cells in situ express exceptionally high levels of endogenous HS in order to execute similar prosurvival functions in vivo.…”
Section: Figurementioning
confidence: 99%
“…Explant-induced apoptosis of glomerular cells was similarly protected by acute treatment with heparin in vitro (42), and we speculate that this early damage may also be attributable to matrix detachment. Furthermore, ultra-low-molecular weight heparin has been reported to prevent glutamate-induced apoptosis in brain cortical cells in vitro and to prevent free radical-induced damage after ischemia/reperfusion injury in rat brain in vivo (43,44). Our demonstration that HS replacement by heparin rescued β cells from free radical damage and apoptosis in vitro is consistent with these prior reports and with the notion that islets/β cells in situ express exceptionally high levels of endogenous HS in order to execute similar prosurvival functions in vivo.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, LMWH has the ability to regulate cellular apoptosis (Yu et al. 2008). LMWH reduces leucocyte recruitment at the site of injury or inflammatory stimuli through the downregulation of the expression of cytokines, tumour necrosis factor (TNF)-α, endotoxins, human leukocyte elastase (HLE), and heparinase (Lever and Page 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ULMWH can obviously reduce Aβ25-35-induced neurotoxic effects and might act as a potential agent for Alzheimer’s disease [2]. ULMWH can also antagonize glutamate-induced apoptosis in cortical cells through a decrease of Ca 2+ release and modulation of apoptotic processes [3]. Our previous study [4] showed the beneficial effects of ULMWH on ischemia-reperfusion injury in rats by decreasing infarct, reducing the neurologic deficit, inhibiting Ca 2+ accumulation, decreasing MDA content and increasing SOD activity in ischemic brain.…”
Section: Introductionmentioning
confidence: 99%